HUBUNGAN MINAT BELAJAR DAN LINGKUNGAN BELAJAR DI RUMAH DENGAN HASIL BELAJAR MATEMATKA - Aqila Fitri Hanindhita Hutami; Sumargiyani Sumargiyani (Universitas Muhammadiyah Semarang, 2018)
The background of this research by the low level student learning interest, less condusive learning environment in students homes, and the low learning outcomes of mathematics. The aims of this research to find out whether or not there is a positive and significant relationship between Learning Interest and Learning Environment at Home with Class X Mathematics Learning Outcomes of MIPA SMA Negeri 3 Cialacap Even Semester Academic Year 2017/2018. The samples were taken by random sampling technique and selected class X MIPA 1 as the sample class. Technique of collecting data:test and questionnaire method.Instruments testing: validity, different power, and reliability test. Prerequisite test analysis: normality test, independent test, and linearity test. Analysis of the data simple regression analysis and multiple correlation analysis regression.The results showed that there was positive and significant relationship between learning interest and the learning environment at homewith Class X mathematics learning Outcomes of MIPA SMA Negeri 3 Cialacapeven semester academic year of 2017/2018.This is indicated by = 3,479 > = 3,285dengan R=0,417 , R2 = 0,174, = −13,619 + 0,387 + 0,648, SR =29,130%, SR = 70,870%, SE = 5,073%, dan SE = 12,342%. Keywords: Learning Interest, Learning Environment at Home, Mathematics Learning Outcomes.